Implementasi Aplikasi Duolingo Dalam Meningkatkan Kosakata Bahasa Inggris Pada Siswa SMPN 19 Mataram - Rahmawati, Lela (CV Insan Kreasi Media, 2024)
The objective of this research is to enhance English language proficiency, with a particular emphasis on vocabulary, through the utilization of the Duolingo application. This application is a gamification application, which means that users can learn English using visual and auditory methods, much like playing a game. This quantitative research method employs a pre-experimental design, which includes a pre-test and post-test for a single group. The objective is to determine the effect of the application of Duolingo applications as a means of enhancing the vocabulary knowledge of students in class VII at SMPN 19 Mataram. The investigation included a total of 150 students in classes VII A to E, with each class consisting of students. The sample was class A, which was composed of 30 students who were randomly selected through randomization. The research data is collected by administering a pre-test and post-test to assess the learning results of vocabulary subjects. Normality tests, descriptive statistics, and T tests are employed in data analysis. The study's findings indicated that the average post-test score (70, 18) was higher than the pre-test average score. (30,78). The standard level of significance of 0.05 is used to determine whether the zero hypothesis can be rejected by contrasting the p-value. The p-value is less than 0.05, with a value of 0.000. This implies that the zero hypothesis is unfeasible, and it is inferred that the Duolingo Application is effective in enhancing student vocabulary knowledge. This is attributed to the presence of supportive elements, such as the analysis of initial skills, the attraction of student attention or motivation, and the improvement of English scores.